Kenakalan pada remaja: Bagaimana peranan kontrol diri ? - Tasya Salsa Billa Azzahra; IGAA Noviekayati; Amherstia Pasca Rina (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to determine the relationship between self-control and delinquency in early adolescent junior high school students. This study used quantitative research with a total of 102 subjects. The sampling technique in this study used a cluster random sampling technique. The research samples included in this study were grades 7A, 8D, and 9E at SMP Cahaya Surabaya. Based on the calculation of the results of data analysis using the Kolmogorov-Smirnov technique, the results of the correlation test were -0.339 with p = 0.000 (p <0.05). This means that there is a significant negative relationship between self-control and delinquency in early adolescent in junior high school students. This means the higher the self-control possessed by adolescents, the lower the tendency to commit delinquency. Thus, the hypothesis in this test can be accepted. Keywords: Juvenile Delinquency, Self Control, Junior High School Students